The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1108/et-09-2020-0278
|View full text |Cite
|
Sign up to set email alerts
|

Can gamification and interface design aesthetics lead to MOOCs' success?

Abstract: PurposeThe purpose of this study is to propose an integrated post-adoption model based on expectation-confirmation model (ECM) and flow theory to examine whether gamification and interface design aesthetics as antecedents to students' beliefs can affect their continuance intention of massive open online courses (MOOCs) and perceived impact on learning.Design/methodology/approachSample data for this study were collected from students enrolled in a comprehensive university in Taiwan. A total of 600 questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 108 publications
4
16
0
Order By: Relevance
“…Insights, implications and future research Overall, the two cases studies indicate that when "ownership" of is transfers to students then gamification can engage students, impart knowledge and develop cognitive and affective competencies in entrepreneurial students. These findings complement and contribute to the extant literature on gamification (Cheong et al, 2014;Cheng, 2021;Buckley, 2015;Alsawaier, 2018;Albertazzi et al, 2019;Isabelle, 2020;Karakoç et al, 2020), entrepreneurial education (Neck and Greene, 2011;Nabi et al, 2017;Longva and Foss, 2018;Borges et al, 2021) and technology enhanced pedagogy specifically within entrepreneurial education (Antonaci et al, 2015;Henry et al, 2005;Lack eus and Middleton, 2015;Chen et al, 2021;Kauppinen and Choudhary, 2021). Study one explored student perceptions of the usefulness of gamification, allowing them to analyse gamification as a tool and apply their knowledge accordingly.…”
Section: Gamification and Entrepreneurial Educationsupporting
confidence: 59%
“…Insights, implications and future research Overall, the two cases studies indicate that when "ownership" of is transfers to students then gamification can engage students, impart knowledge and develop cognitive and affective competencies in entrepreneurial students. These findings complement and contribute to the extant literature on gamification (Cheong et al, 2014;Cheng, 2021;Buckley, 2015;Alsawaier, 2018;Albertazzi et al, 2019;Isabelle, 2020;Karakoç et al, 2020), entrepreneurial education (Neck and Greene, 2011;Nabi et al, 2017;Longva and Foss, 2018;Borges et al, 2021) and technology enhanced pedagogy specifically within entrepreneurial education (Antonaci et al, 2015;Henry et al, 2005;Lack eus and Middleton, 2015;Chen et al, 2021;Kauppinen and Choudhary, 2021). Study one explored student perceptions of the usefulness of gamification, allowing them to analyse gamification as a tool and apply their knowledge accordingly.…”
Section: Gamification and Entrepreneurial Educationsupporting
confidence: 59%
“…Evidence from another reviewed study (Tongpaeng et al, 2019 ) suggested that implementation of shorter learning videos (below six minutes) and interactive media increased not only engagement, but also the learner's achievement in MOOCs. It should also be noted here that to increase students’ satisfaction and solve the high dropout problem in the online learning management system, or MOOCs, educational institutions, educational system designers, and instructors should design learner-centred gamification mechanisms that take students' learning requirements into consideration (Cheng, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the e-learning context, students’ increased usage of the learning management system can cause enhancements in their perceived impact on learning (McGill & Klobas, 2009). Further, students’ continuance intention of MOOCs can positively result in their perceived impact on learning (Cheng, 2021). Thus, this study posits that learners’ continuance intention of MOOCs has a positive effect on their perceived impact on learning.…”
Section: Hypotheses Development and Research Modelmentioning
confidence: 99%
“…Noteworthily, gamification is one of the most vital strategies that have attracted the attention of MOOC practitioners during the recent years, because they believe that it is more useful to transform learning resources to be more game-like to increase learners’ motivation to engage in MOOCs (Aparicio et al, 2019; Poondej & Lerdpornkulrat, 2020). Thus, gamification features may be introduced to MOOCs as the environmental stimuli of improving learners’ motivation and usage intention towards using MOOCs (Aparicio et al, 2019; Cheng, 2021). To date, there is still a lack of knowledge regarding how gamification features influence learners’ MOOCs continuance intention after having initially accepted it, while MOOCs have been regarded as a more innovative tool for delivering information and knowledge within educational sectors (Aparicio et al, 2019).…”
mentioning
confidence: 99%